Persebaran, Populasi dan Persentase Serangan Citripestis Sagittiferella Moore (Lepidoptera: Pyralidae) Pada Buah Jeruk Besar di Kabupaten Bangli dan Gianyar - KADEK ADI MARTHANA; I GUSTI NGURAH BAGUS; I WAYAN SUSILA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2018)
The Distribution, Population and Damage Percentage of Citripestis Sagittiferella Moore (Lepidoptera: Pyralidae) on Large Citrus Fruits in Bangli and Gianyar Regencies This research was conducted in Bangli (Kintamani District) and Gianyar Regencies (Sukawati, and Payangan Districts), and in Integrated Pest Management and Disease Laboratory, Faculty of Agriculture, Udayana University, from December 2017 to February 2018. The purpose of this research are to know the distribution, population and demage percentage of citrus borer, Citripestis sagittiferella. This research used a survey method. The research area was divided into three altitudes, Sukawati District (0-450 m asl), Payangan District (altidute> 450-800 m asl), and Kintamani District (altidute>800-1000 m asl). The results showed that C. sagittiferella was found evenly distributed in all altitude locations, in Sukawati District, Payangan District and Kintamani District with total population of 3684 larvae, 2152 larvae and 916 larvae respectively. The average larva population found in citrus fruits damage was 6.28 larvae per fruit. Percentage of damage in Kintamani, Payangan, and Sukawati Districts were 30.37%, 25.26%, and 18.18%, respectively. The correlation test results show a very strong correlation between the larval population and the percentage of damage with r = 0.988.